PENGETAHUAN, SIKAP DAN PERILAKU MASYARAKAT TERHADAP MALARIA DI KOTA BATAM - Manalu, Helper Sahat P; Sukowati, Supratman (Badan Penelitian dan Pengembangan Kesehatan, 2011)
Malaria remains a major public health problem and causes outbreaks and re-emerging of malaria in places which previously had been declared to be malaria free in Indonesia. Malaria is very important issue in tourist industry, socio-economic impact and poverty. There are some risk factors of malaria transmission e.g. physical environment changes including the climate change such as rainfall, temperature, land used, environment deterioration; poverty, mobility of people and economic crisis. The understanding of knowledge, attitude and practices of the community in malaria and its control are very important for its prevention and control strategy. This paper presented the study of knowledge, attitude and practices on malaria, prevention its control in year 2008 in Batam area. There were 248 respondents surveyed from three sub-district, consist of 84 respondents from Nongsa, 89 respondents from Galang sub-district and 75 respondents from Belakang Padang. Quantitative and qualitative data were collected by using structural questionnaire for the community and personal in-dept interview for the community leaders. The results of the study shows that most of the respondents understand and ever heard about malaria (91.9%); nevertheless most of them do not have good attitude in malaria prevention and control (97.6%). There was 82.3% of respondents have being outdoor during the night time, beside there was 39.5% respondents stayed overnight outdoor. These KAP situation of the community in malaria endemic area will increase the malaria transmission risk. However, to improve the knowledge, attitude, and practices for prevention and control of malaria, the program of health promotion should be improved and keep sustainiing.